Ti3C2Tx MXene‐Zirconium Diboride Based Ultra‐High Temperature Ceramics - Srinivasa Kartik Nemani; Nicola Gilli; Steven Goldy; Ankit Kumar; Yooran Im; Austin J. Vorhees; Brian C. Wyatt; Nithin Chandran BS; Nikhilesh Chawla; Garritt J. Tucker; Laura Silvestroni; Babak Anasori (Advanced Science)
Abstract MXenes are a family of two‐dimensional (2D) transition metal carbides, nitrides, and carbonitrides with potential applications in ceramics and composites due to their nanometer‐thick morphology, hydrophilic surfaces, and negative zeta potentials. In this study, we investigated titanium carbide MXene (Ti3C2Tx) as an additive in ultra‐high‐temperature ceramics (UHTCs), specifically zirconium diboride (ZrB2). Homogeneous green bodies of Ti3C2Tx and ZrB2 were synthesized via electrostatic self‐assembly in aqueous media without surfactants and subsequently densified using field‐assisted (spark plasma) sintering. The incorporation of 0.5 wt.% MXene enhanced the relative density of ZrB2 from ≈89% (pure ZrB2) to ≈96% under identical sintering conditions. MXene addition significantly reduced the oxygen content from ≈5 at.% in pure ZrB₂ to ≈2–3 at.% at 2.5 wt.% MXene loading. The presence of MXene also facilitates the formation of a core–shell microstructure, where (Zr,Ti)B2 shells encapsulate ZrB₂ cores, with arrays of dislocations observed at the core–shell interface. Mechanical characterizations show substantial improvements, including a 36% increase in hardness, a ≈12% enhancement in Young's modulus, and a ≈15% increase in flexural strength at 2.5 wt.% MXene loading. These findings demonstrate the potential of MXenes as effective sintering aids and reinforcement agents in UHTCs, offering promising pathways for advancing materials designed for extreme environments.